# Solve for m -3(2m-5)=1/2*(-12m+30) -3(2m-5)=12⋅(-12m+30)
Simplify -3(2m-5).
Apply the distributive property.
-3(2m)-3⋅-5=12⋅(-12m+30)
Multiply.
Multiply 2 by -3.
-6m-3⋅-5=12⋅(-12m+30)
Multiply -3 by -5.
-6m+15=12⋅(-12m+30)
-6m+15=12⋅(-12m+30)
-6m+15=12⋅(-12m+30)
Simplify 12⋅(-12m+30).
Apply the distributive property.
-6m+15=12(-12m)+12⋅30
Cancel the common factor of 2.
Factor 2 out of -12m.
-6m+15=12(2(-6m))+12⋅30
Cancel the common factor.
-6m+15=12(2(-6m))+12⋅30
Rewrite the expression.
-6m+15=-6m+12⋅30
-6m+15=-6m+12⋅30
Cancel the common factor of 2.
Factor 2 out of 30.
-6m+15=-6m+12⋅(2(15))
Cancel the common factor.
-6m+15=-6m+12⋅(2⋅15)
Rewrite the expression.
-6m+15=-6m+15
-6m+15=-6m+15
-6m+15=-6m+15
Move all terms containing m to the left side of the equation.
Add 6m to both sides of the equation.
-6m+15+6m=15
Combine the opposite terms in -6m+15+6m.
0+15=15
15=15
15=15
15=15
Since 15=15, the equation will always be true for any value of m.
All real numbers
The result can be shown in multiple forms.
All real numbers
Interval Notation:
(-∞,∞)
Solve for m -3(2m-5)=1/2*(-12m+30)

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top